A survey of academic staff attitudes towards the system of academic titles used in New Zealand universities - Cavana, Bob; Crozier, Rob; Davis, Barrie; Pillai, Perumal (School of Management Working Papers, 1995)
This report presents the results of a survey of academic staff at New Zealand universities to determine their attitudes towards a change in academic titles from the current British system to the US system. A questionnaire was developed and sent to a stratified random sample of 1340 academic staff selected from the 7 universities in New Zealand. A total of 671 valid responses was received. The responses were analysed statistically by university, faculty, designation, qualifications, gender, age and overseas experience. The comments were also analysed qualitatively. The overall results indicated that 44% of the respondents preferred the current system of titles, 39% preferred the alternative US system and 17% did not have a preference. However, the differences between the preferences for the two systems were not significant at the 95% ( or 90%) confidence level. The analysis by university revealed that although academic staff at Auckland and Victoria Universities generally preferred the alternative US system and academic staff at Canterbury, Lincoln and Otago Universities generally preferred the current system of academic titles, only responses from Massey and Waikato Universities indicated a statistically significant preference for the current system. Staff in the "professional" faculties (eg Agriculture, Commerce and Law) generally preferred the alternative US system, compared with academics from the more "traditional" academic areas (eg Humanities/Arts and Social Sciences) who tended to prefer the current British system. However, the only statistically significant differences were recorded by Medical/Dental academic staff who overwhelmingly indicated a preference for the current system. The results also indicated that staff who were born or had their main overseas academic experiences in Commonwealth countries (eg NZ, Australia and UK) tended to prefer the current British system of academic titles, whereas staff who were born or had their main overseas academic experiences in generally non-Commonwealth countries (eg in Asia, Europe (excl. UK) and North America) preferred the alternative US system. Professors and assistant/junior lecturers showed a statistically significant preference for the current system whereas, overall, senior lecturers tended to prefer the alternative system (although not statistically significant). Generally the results indicate that there is not a majority support for either the British or the US systems of academic titles and there is a considerable level of dissatisfaction with the current system. Consequently it is concluded that more research needs to be undertaken to determine the best system of academic titles and salary scales for academic staff at New Zealand universities.